2019
DOI: 10.1177/1120672119891415
|View full text |Cite
|
Sign up to set email alerts
|

Amniotic membrane for retinal detachment due to paravascular retinal breaks over patchy chorioretinal atrophy in pathologic myopia

Abstract: Purpose: To describe a new surgical technique, using a human amniotic membrane patch, in two cases of retinal detachment with paravascular retinal breaks over patchy chorioretinal atrophy in pathologic myopia, already underwent pars plana vitrectomy with the internal limiting membrane peeling for myopic foveoschisis. Methods: Surgical technique description with surgical video. A 23-gauge pars plana vitrectomy was performed. A human amniotic membrane patch was implanted under the neuroretina to seal the posteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…Here, we have demonstrated that the combination of a PRP and hAM have a synergistic effect and an enhanced clinical outcome for pathologic myopia. Although the PRP preparation represents an additional step in the surgical procedure, its use permits the reduction of post-operatory face down position from 1 week, as reported by Rizzo et al, 14 to 3 days, thus being better tolerated by the patient.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Here, we have demonstrated that the combination of a PRP and hAM have a synergistic effect and an enhanced clinical outcome for pathologic myopia. Although the PRP preparation represents an additional step in the surgical procedure, its use permits the reduction of post-operatory face down position from 1 week, as reported by Rizzo et al, 14 to 3 days, thus being better tolerated by the patient.…”
Section: Discussionmentioning
confidence: 92%
“…11 Retinal hAM plug transplantation has been recently successfully used for the management of high myopic macular hole 12,13 and retinal breaks. 14,15…”
Section: Discussionmentioning
confidence: 99%
“…They reported two cases out of two of retinal reattachment. The BCVA improved from 20/2000 to 20/250 [ 33 ].…”
Section: Outcomes Of the Human Amniotic Membrane Retinal Transplanmentioning
confidence: 99%
“…The hAM application for retinal pathologies was extended to treat large macular tears [ 31 ], high myopic retinal detachment associated with MH [ 32 ], paravascular tears [ 33 ], serous macular detachment associated with optic pits [ 34 ], complicated retinal detachment [ 30 ] and advanced age related macular degeneration (AMD) [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human amniotic membrane (HAM) has been reported to be safe for intraocular use; moreover, as Rizzo et al described, it appears to promote retinal healing [6][7][8]. Lyophilization of HAM maintains its histological structure [9] and, at the same time, confers beneficial features regarding its storage, biosafety and surgical handling.…”
Section: Open Accessmentioning
confidence: 99%